Some fixed point theorems in ordered partial metric spaces with applications. Issue 1 (1st January 2018) - Eke, Kanayo Stella; Oghonyon, Jimevwo Godwin
Abstract: We defined the class of generalized weakly C-contractive mappings in partial metric spaces and proved some fixed-point results for such maps in ordered partial metric spaces without exploiting the continuity of any of the functions. We also establish fixed-point theorem for the integral type of these maps. Example is given to support the validity of our result. Our result generalizes the results of Chen and Zhu [3] and others in the literature